Improving infant and young child feeding practices through self-help groups in Bihar: The experience of the Parivartan initiative - Das, Rajshree; Sarangi, Biraj; Rao, Brijesh; Schooley, Janine (International Food Policy Research Institute, 2015)
Based on global standards for nutrition, the National Rural Health Mission of India recommends complementary feeding to infants at six months to ensure optimum growth and development (NRHM 2012). However, in much of India, that target is not being reached. In an assessment of complementary feeding practices in Bihar, researchers found that only 58 percent children received any complementary foods at six months (Khan et al 2013).